Effectiveness of American Society of Perianesthesia Nurses (ASPAN) on Maternal and Neonates Outcome during Perioperative Enhanced Recovery after Caesarean Surgery (ERACS) - mustakim; Ika Yuni Widyawati; Sigit Sugiharto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Introduction. Patient comfort is one of the important components that must be considered in providing nursing care, including perioperative nursing services, one of which is temperature comfort. The purpose of this research is to explain or to study the effect of the ASPAN guideline intervention for normothermia (active and passive warming) on ​​maternal and neonates outcomes during perioperative Enhanced Recovery After Caesarean Surgery (ERACS). Method. This research used a quasi-experimental quantitative research design or a quasi-experiment involving a control group and an intervention group. Measurement of the intervention group for prevention of hypothermia in cesarean section patients was performed perioperatively (pre-intra-post-surgery). Results. The mother's body temperature variable in the intraoperative and postoperative phases was higher in the intervention group than the control group. The shivering condition variable in the control group experienced an increase in shivering during the intraoperative and postoperative phases (1.15 ± 0.41 and 2.17 ± 0.80), while in the intervention group there was a decrease in shivering condition (0.22 ± 0, 42 and 0.20 ± 0.41). In the temperature comfort variable after measuring using Thermal Comfort ERACS, the Mean ± SD value in the intervention group when the intra-operative and post-operative phases was in the neutral category (0.44 ± 0.6 and 0.44 ± 0.65). Discussion & Conclusion. Application of ASPAN Guideline for normothermia during perioperative obtained significant results on the variable of the mother's temperature, the baby's temperature.